"Żydzi", którzy uwierzyli Jezusowi - Wróbel, Mirosław Stanisław (Verbum Vitae, 2004)
In polemical dialogue Jn 8:31-59 the expression about "the Jews w ho had believed in Jesus" (v. 31) seems to contradict what Jesus himself says later in the text. This problem can be resolved by translating the perfect participle as the pluperfect. In this case the expression in Jn 8:31 may be referred to those who had believed but who now believe no longer. The analysis of this expression shows the importance of the concept of faith in the Fourth Gospel. The process of faith of persons who meet Jesus is contrasted with those who do not believe. In the background of ethical and apocalyptical dualism the author of the Fourth Gospel wanted to show the dynamism ofthe faith and its existential nature.